Combined locoregional treatment of patients with hepatocellular carcinoma: State of the art - Iezzi, Roberto (World J Gastroenterol, 2016)
In recent years, a combination of intervention therapies has been widely applied in the treatment of hepatocellular carcinoma (HCC). One such combined strategy is based on the combination of the percutaneous approach, such as radiofrequency ablation (RFA), and the intra-arterial locoregional approach, such as trans-arterial chemoembolization (TACE). Several types of evidence have supported the feasibility and benefit of combined therapy, despite some studies reporting conflicting results and outcomes. The aim of this review was to explain the technical aspects of different combined treatments and to comprehensively analyze and compare the clinical efficacy and safety of this combined treatment option and monotherapy, either as TACE or RFA alone, in order to provide clinicians with an unbiased opinion and valuable information. Based on a literature review and our experience, combined treatment seems to be a safe and effective option in the treatment of patients with early/intermediate HCC when surgical resection is not feasible; furthermore, this approach provides better results than RFA and TACE alone for the treatment of large HCC, defined as those exceeding 3 cm in size. It can also expand the indication for RFA to previously contraindicated “complex cases”, with increased risk of thermal ablation related complications due to tumor location, or to “complex patients” with high bleeding risk.